Kinetic sequencing (k-Seq) as a massively parallel assay for ribozyme kinetics: utility and critical parameters. Issue 12 (27th March 2021) - Shen, Yuning; Pressman, Abe; Janzen, Evan; Chen, Irene A
Abstract: Characterizing genotype-phenotype relationships of biomolecules (e.g. ribozymes) requires accurate ways to measure activity for a large set of molecules. Kinetic measurement using high-throughput sequencing (e.g. k -Seq) is an emerging assay applicable in various domains that potentially scales up measurement throughput to over 10 6 unique nucleic acid sequences. However, maximizing the return of such assays requires understanding the technical challenges introduced by sequence heterogeneity and DNA sequencing. We characterized the k -Seq method in terms of model identifiability, effects of sequencing error, accuracy and precision using simulated datasets and experimental data from a variant pool constructed from previously identified ribozymes. Relative abundance, kinetic coefficients, and measurement noise were found to affect the measurement of each sequence. We introduced bootstrapping to robustly quantify the uncertainty in estimating model parameters and proposed interpretable metrics to quantify model identifiability. These efforts enabled the rigorous reporting of data quality for individual sequences in k -Seq experiments. Here we present detailed protocols, define critical experimental factors, and identify general guidelines to maximize the number of sequences and their measurement accuracy from k -Seq data. Analogous practices could be applied to improve the rigor of other sequencing-based assays.